Atmospheric circulation influence on climatic trends in Europe: an analysis of circulation type classifications from the COST733 catalogue. (7th April 2014) - Cahynová, Monika; Huth, Radan
ABSTRACT: We studied the influence of changes in the frequency of atmospheric circulation types (CTs) on seasonal trends of daily maximum and minimum temperature and precipitation at several European stations in the period 1961–2000. The 24 circulation classifications used were created within the COST733cat database using eight classification methods; each applied on daily sea‐level pressure fields over Europe and 11 smaller European domains in three variants with fixed numbers of types (9, 18, and 27). This allows us to study how different spatial scales of circulation and varying numbers of CTs affect the circulation–climate relationship. Significant trends in the frequency of CTs took place mainly in winter, and these clearly reflect the tendency towards positive phase of the North Atlantic Oscillation: the frequency of westerly types increased in the central latitudinal belt from the British Isles east to Ukraine, whereas the frequency of days with cyclonic circulation increased over Iceland and decreased in central Mediterranean. Seasonal temperature and precipitation trends can be only partly explained by the changing frequency of CTs, the link being the strongest in winter. In spring, summer, and autumn, the observed climatic trends are not forced by changes in the frequency of CTs but rather by changing climate within these types, which confirms the previously reported nonstationarities in the relationship between atmospheric circulation and local climate. There are marked differences among the results obtained using 24 parallel, fully comparable objective catalogues of CTs, but neither good or bad result nor any preferred classification method can be discerned. In winter and spring, small‐scale circulation influences the observed climatic trends more than large‐scale circulation on a majority of stations except for Iceland and Scandinavia. Classifications with more CTs usually explain a larger proportion of the observed climatic trends.